Giving the force direction: Analysis of speed skater push off forces with respect to an inertial coordinate system - van der Kruk, E.; van der Helm, F. C. T.; schwab, A. L.; Veeger, H. E. J. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
Push-off in speed skating requires an extensive motion strategy. During speed skating the skater continuously changes the lean and steering angle of the skate and therewith the direction of push-off, The forces in an inertial coordinate system can give insight into what amount of the push-off force is directed into the forward motion. In this paper we present the preliminary results of a study on the global forces in speed skating. From a mechanical viewpoint, increasing the lean angle of the skate seems beneficial at the end of the stroke, but detrimental at the start of the stroke. Furthermore the necessity of the lateral force on the skate in the overall force production is a variable of interest for further investigation, since dynamically it has a disadvantageous effect on the forward motion.